Stochastic Nonlinear Thermoelastic System Coupled Sine-Gordon Equation Driven by Jump Noise. (24th February 2014) - Cheng, Shuilin; Guo, Yantao; Tang, Yanbin
Abstract : This paper considers a stochastic nonlinear thermoelastic system coupled sine-Gordon equation driven by jump noise. We first prove the existence and uniqueness of strong probabilistic solution of an initial-boundary value problem with homogeneous Dirichlet boundary conditions. Then we give an asymptotic behavior of the solution.